Jenis, Metode dan Pendekatan Dalam Penelitian Hukum - Mezak, Meray Hendrik (Pelita Harapan University, 2006)
Research is an effort to search and reveal truth in science including law. That is the reason why law as part of science also possesses and follows its own method. As a custom, law has is catagorized as part of social science and follow the methodology of social science. In reality law has its own specification where the inquiry is based on normative law and substance is not merely empirical evidence. For that reason legal research can not be regarded as following the methodology of social sciences in general.